Performance optimization of InGaAs power LDMOSFET. Issue 5 (May 2015) - Singh, Yashvir; Badiyari, Mukesh
Abstract In this paper, a power laterally diffused metal-oxide-semiconductor field-effect transistor (LDMOSFET) on InGaAs is proposed to achieve substantial improvement in breakdown voltage, on-resistance and Baliga׳s figure-of-merit with reduced cell pitch. The proposed LDMOSFET contains two vertical gates which are placed in two separate trenches built in the drift region. The source and drain contacts are taken from the top. The modified device has a planer structure implemented on InGaAs which is suitable for medium voltage power integrated circuits. The performance of proposed device is evaluated using two-dimensional numerical simulations and results are compared with that of the conventional LDMOSFET. The proposed structure considerably reduces the electric field inside the drift region due to reduced-surface field (RESURF) effect even at increased doping concentration leading to improved design trade-off. The proposed device provides 144% higher breakdown voltage, 25% lower specific on-resistance, 8 times improvement in figure-of-merit, and 25% reduction in cell pitch as compared to the conventional device.